Estudo químico de plantas do gênero Hortia, do fungo Guignardia citricarpa e avaliação de seus potenciais efeitos biológicos - Severino, Vanessa Gisele Pasqualotto (2011)
The chemical investigation of plants belonging to the genus Hortia described here aimed at contributing to the chemosystematics of the family Rutaceae as well as to the correct placement of this genus within this family. Study involving the species H. oreadica Groppo, Kallunki and Pirani; H. brasiliana Vand. ex DC.; and H. superba Ducke led to the isolation of 21 compounds, more specifically ten limonoids, three dihydrocinnamic acid derivatives, five alkaloids (two furan quinolinic, one 2-quinolone, and two indoloquinazolinone) and three coumarins (one linear furanocoumarin and two angular pyranocoumarins). Taking together all the data obtained on secondary metabolites from the genus Hortia in the present study as well as in previous works, it was possible to propose the positioning of this genus in the intersection of Rutoideae and Toddalioideae, but close to Flindersioideae. Various biological assays were conducted by using plant extracts and isolated compounds from three Hortia species, and the most significant activities were detected for rutaecarpine (against Xylella fastidiosa and Mycobacterium tuberculosis) and N-methyl-4-methoxy-2-quinolone (against Guignardia citircarpa); for the limonoids hortiolide C (against X. fastidiosa and Streptococccus sanguinis), hortiolide D (against Streptococccus salivarius), and hortiolide E (against S. sanguinis and S. salivarius); for the dihydrocinnamic acid derivative 3-[2,6-dimethoxy-6´,6´-dimethylpyran- (2´,3´:4,5)-phenyl]-propionic acid (against M. tuberculosis and G. citricarpa); and for the coumarin 5-methoxy-seseline (against G. citricarpa). Investigation of the phytopathogenic fungus G. citricarpa aimed at acquiring knowledge about the chemistry of this microorganism. After optimization of the liquid culture medium (potato-dextrose, Czapeck and Czapeck enriched with 2% malt extract) and growth period (05 to 45 days) appropriate for G. citricarpa, this fungus was developed at a larger scale using potato-dextrose for 25 to 35 days. The crude extracts were submitted to fractionation by chromatography, which furnished 13 different compounds of different classes of secondary metabolites, namely four diketopiperazines [cyclo-(proline-leucine), cyclo-(phenylalaninetyrosine), cyclo-(proline-tyrosine), and cyclo- (proline-phenylalanine)], one nitrogen base (uracil), three nucleosides (uridine, 5-methyl-uridine, and inosine), one amino acid (tryptophan), one aromatic alcohol (tyrosol), one furfuraldehyde (5-hydroxy-methyl-furfuraldehyde), one benzoic acid derivative (4-hydroxybenzoic acid), and one triglyceride. The isolation of tyrosol motivated new investigations on its possible role in pathogenicity events in Citrus, since there are some literature reports on its signaling and autoregulation activities in some endophytic fungi. Crude extracts from G. citricarpa were assayed against X. fastidiosa. The results revealed promising MIC values, prompting continuation of this study. In conclusion, the work described in this thesis has demonstrated that some natural compounds displaying antimicrobial activity have potential application as lead compounds for the discovery of novel bioactive compounds.